Tindak Pidana Pencurian Dengan Kekerasan : Studi Putusan Nomor 1475/Pid.B/2023/PN Mdn - Cristian Agave Siregar; Gracia Veronica Siregar; Siti Anisah Nasution; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu (Pusat Riset dan Inovasi Nasional, 2023)
Violent theft is indeed a crime that makes society restless. The person who committed the crime was indeed from the element of coercion against him. The person dares to do so because of the weak economy and always expects a wealth that takes from someone else's. As will be discussed in this journal regarding cases of violent criminal acts decision number 1475 / Pid.B / 2023 / PN Mdn. This study contains its object regarding the crime of theft with violence, using a juridical-normative type of legal research, meaning that the legal research studied only uses secondary data or library materials. The problem that the author wants to study is how the stages of implementing the case process of decision number 1475/pid.b/2023/pn/mdn based on the criminal procedure law and what are the factors that cause a person's desire to commit theft. Thus, the defendant was sentenced to imprisonment for 3 years and was required to pay a case fee of Rp 5,000. The judge's judgment in sentencing is based on juridical and non-juridical considerations. Juridical considerations involve valid and convincing evidence showing that the accused clearly fulfilled all elements of the crime of violent theft as stipulated in article 365 paragraph (2) 2e of the Penal Code. Meanwhile, non-juridical considerations involve social values and judgments on the character of the accused, as well as factors that may aggravate or mitigate the sentence to be imposed by the judge.